2015
DOI: 10.1007/s40626-015-0031-9
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic traits of tree species in response to leaf nutrient content in the central Amazon

Abstract: Rainforest tree species are often found on poor soils where essential nutrients may be in low concentrations. Here, we determine the effect of nutrients (N, P, Ca, Mg and K) in photosynthetic traits in five rainforest tree species from central Amazonia. Gas exchange parameters were measured with an infrared gas analyzer in four saplings (1-3 m tall) per species using two leaves per plant. Data on gas exchange and leaf nutrient content (N, P, K, Ca and Mg) were collected between August and November, 2010. Speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
5
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 44 publications
5
5
1
4
Order By: Relevance
“…Leaf nutrient contents found in this study are similar to those reported by Mendes & Marenco (2015). Except for leaf P concentration, the mean values of leaf nutrient content for N, K, Ca and Mg found in this study resemble those reported by Fyllas et al (2009) for tropical trees.…”
Section: Leaf Nutrient Contentsupporting
confidence: 89%
See 4 more Smart Citations
“…Leaf nutrient contents found in this study are similar to those reported by Mendes & Marenco (2015). Except for leaf P concentration, the mean values of leaf nutrient content for N, K, Ca and Mg found in this study resemble those reported by Fyllas et al (2009) for tropical trees.…”
Section: Leaf Nutrient Contentsupporting
confidence: 89%
“…Therefore, data collected over seasons were combined for data analysis. In comparison with L T , SLA varied only within a narrow range, from 14.3 to 20.5 m 2 kg -1 (Table 2), which is within the range observed in other tree species in the same region (Marenco & Vieira, 2005, Mendes & Marenco, 2015. There was no difference among species on AIH, AID or ∆B ( Table 2), indicating that differences on growth rates across microsites were related to environmental factors rather than differences on the genetic make-up of the species.…”
Section: Leaf Traits and Sapling Growthsupporting
confidence: 79%
See 3 more Smart Citations